Modelagem e simulação de um sistema de bombeio mecânico em poços direcionais utilizando parâmetros concentrados - Lins, Filipe Campos de Alcantara (2010)
This work aims presenting the development of a model and computer simulation of a sucker rod pumping system. This system take into account the well geometry, the flow through the tubing, the dynamic behavior of the rod string and the use of a induction motor model. The rod string were modeled using concentrated parameters, allowing the use of ordinary differential equations systems to simulate it s behavior